1/f Noise in Mott Variable Range Hopping Conduction in p-type Amorphous Silicon. Issue 1770 (1st June 2015) - Lopes, V.C.; Syllaios, A.J.; Whitfield, D.; Shrestha, K.; Littler, C.L.
ABSTRACT: We report on electrical conductivity and noise measurements made on p-type hydrogenated amorphous silicon (a-Si:H) thin films prepared by Plasma Enhanced Chemical Vapor Deposition (PECVD). The temperature dependent electrical conductivity can be described by the Mott Variable Range Hopping mechanism. The noise at temperatures lower than ∼ 400K is dominated by a 1/f component which follows the Hooge model and correlates with the Mott conductivity. At high temperatures there is an appreciable G-R noise component.